2020
DOI: 10.15547/bjvm.2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of avian influenza A viruses in Basrah and Wasit

Abstract: The aim of this study was to detect influenza A virus in broiler chickens and wild ducks in different geographical regions of Basrah and Wasit provinces, Iraq. This study was authenticated by analysing the viral genome and designing a set of universal primers for the detection of all influenza A subtypes in a single enzymatic reaction through the amplification of a highly conserved region of viral M gene. A total of 157 and 155 oropharyngeal and cloacal swabs from broiler chickens and wild ducks, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…(2010) from 5 provinces of Iran but much lesser than isolated from the central region of Iran (Majidzadeh et al., 2012). Comparison of our results with those reported from the neighbouring countries revealed that the number of positive cases in our study was less than that recently reported from Iraq (Al‐Badry & Al‐Mubarak, 2020), Turkey (Onmuş, 2008) and Pakistan (Khawaja et al., 2005) but a little more than that reported from Ukraine (Muzyka et al., 2019). However, the important point is that a percentage of waterfowl and migratory birds in the Urmia Lake Basin contains the influenza virus, and this percentage, no matter how small it was (Table 5), is considered a potential threat to native poultry in rural and industrial poultry farms around the shores of Lake Urmia as previously emphasised (Fallah‐Mehrabadi et al., 2016).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…(2010) from 5 provinces of Iran but much lesser than isolated from the central region of Iran (Majidzadeh et al., 2012). Comparison of our results with those reported from the neighbouring countries revealed that the number of positive cases in our study was less than that recently reported from Iraq (Al‐Badry & Al‐Mubarak, 2020), Turkey (Onmuş, 2008) and Pakistan (Khawaja et al., 2005) but a little more than that reported from Ukraine (Muzyka et al., 2019). However, the important point is that a percentage of waterfowl and migratory birds in the Urmia Lake Basin contains the influenza virus, and this percentage, no matter how small it was (Table 5), is considered a potential threat to native poultry in rural and industrial poultry farms around the shores of Lake Urmia as previously emphasised (Fallah‐Mehrabadi et al., 2016).…”
Section: Discussioncontrasting
confidence: 57%
“…Although as a preferred specimens site, the cloaca area is more likely to be sampled and the AI viruses may be isolated (Al‐Badry & Al‐Mubarak, 2020; Killian, 2020; Löndt & Alexander, 2016; OIE, 2021a,b; Spackman & Suarez, 2016), but 3 of 5 positive AIV samples of this study (Table 5) were oropharyngeal (OP) swab samples as previously used (Ssematimba et al., 2018), and this episode could be contributed to different phases in the influenza virus infection process (Germeraad et al., 2019; Wang et al., 2019) indicating that oropharyngeal swab samples like cloaca swab samples contribute to the detection of positive birds, and neither should be neglected (Fereidouni et al., 2010). The percentage of positive cases for AIV observed during this study (Table 5) is a little higher than the results obtained by Fereidouni et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional reverse transcriptase polymerase chain reaction (RT-PCR) method was used to detect the presence of the 3 viruses in the study. For the AIV, a pair of universal primers was used to detect any possible type of the virus [15]. Regarding the other 2 viruses, IBV and NDV, the gene-specific primers were designed using the National Center for Biotechnology Information.…”
Section: Nucleic Acid Detection By Reverse Transcriptase Polymerase C...mentioning
confidence: 99%